Modelling Ebola. (1st June 2016) - Kamalaldin, Kamalaldin; Salome, Amber; Érdi, Péter
This paper is the combination of a review on the problems of data collection and modelling efforts of the recent Ebola epidemics. After a brief review of data availability, the modelling frameworks have been discussed. Both deterministic and stochastic models have been reviewed and supplemented with a short discussion of some problems of parameter estimation. The methods have been illustrated by a realistic case study. A hint is given for the scope and limits of prediction and control.